Discrete-event Simulation Guides Pipeline Logistics - Cafaro, Vanina (2011)
A discrete-event simulation technique, combined with optimization tools, permits easy management of real-world pipeline operations with low computational effort. Modeling to develop the technique used a non-traditional multi-server queuing system with a number of synchronized servers at every pipe-end and priority rules to decide which server should dispatch the entity waiting for service to the associated depot. Each priority rule can lead to a different delivery schedule, evaluated using several criteria. Part 1 of this series discusses a novel discrete event simulation system developed on “Arena” for the detailed scheduling of a multiproduct pipeline consisting of a sequence of pipes connecting a single input station to several receiving terminals. Part 2 will conclude this discussion and apply its findings to management of a real-world multiproduct pipeline.